Study of the potential expansion of new rice fields in Central Maluku District to support food security in Maluku Province - Rusmin Nuryadin; Edy Suryadi; Robby Andoyo; Dwi Rustam Kendarto (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
Maluku province is one of the Islands in Indonesia. Seram island is one of the largest islands in the Maluku province lies the Central Maluku Regency. Central Maluku district is one of the priorities regions in the development of paddy fields in the province of Maluku. According to the BPS Maluku province in the year 2015, Government Maluku province was only able to meet the needs of 58% of the rice. Fulfillment needs rice is one of the Government's efforts in food self-sufficiency, it is because of the availability of food is one of the primary needs. Increased agricultural productivity through the extension of new rice fields became one alternative settlement in fulfillment of rice. The increase in rice production through the expansion of rice fields is still possible, because of the potential land is suitable for the expansion of rice fields was still quite spacious. The success of the process of the expansion of paddy fields depend on the expansion of the activities of the mechanism of the rice is done. The process of the expansion of rice fields is preceded by feasibility investigation location. Feasibility study of the site was conducted to find out the feasibility of potential land with the observations in the field which is then processed and spatial dianalis in using ArcGIS software. Results of a survey investigating the Central Maluku district region with a total area of 594.29 achieved ha based on the suitability of the land for the potential expansion of new acres of rice paddies 587.35 ha from 2 (two) subdistricts include North Eastern Seram Subdistrict Kobi m2 170.87 ha and North Seram Subdistrict covering 416.82 ha. Keywords: The Expansion Of New Rice Fields, Agricultural Land Suitability Evaluation, Islands